Analisis Penerapan Akuntansi Pembelian Dan Penjualan Pada Toko Isabella Pasar Cendrawasih Kota Metro - David Setiawan; Jawoto Nusantoro; Muhammad Ridho Al Amin (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the suitability of the accounting treatment of purchases and sales at the Isabella Pasar Cendrawasih Store, Metro City, with the basic concepts of accounting. The data was obtained from the store manager and the daily record book (cash book) of the shop owner. Analysis of the research data was carried out using descriptive analysis. The results of this study indicate that the basis of record used by the clothing store entrepreneur is the cash basis, which recognizes or records transactions when cash is received or paid, and the accrual basis, which recognizes or records them when they occur. Clothing store entrepreneurs have not fulfilled the concept of business unity because they have not carried out financial separation.